Roasting treatments affect oil extraction rate, fatty acids, oxidative stability, antioxidant activity, and flavor of walnut oil - Li, Huankang; Han, Jiajia; Zhao, Zhongkai; Tian, Jinhu; Fu, Xizhe; Zhao, Yue; Wei, Changqing; Liu, Wenyu (Frontiers in Nutrition, 2023)
Introduction The quality of pressed walnut oil can be improved by moderate roasting treatment. Methods This study compared physicochemical characteristics and antioxidant ability of walnut oils pressed from differently roasted pretreated walnuts, analyzed the correlation among these indicators by using Pearson correlation coefficient and correlation coefficient heatmap, and evaluated the volatile organic compounds (VOCs) of walnut oil under optimal pretreatment roasting conditions using headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS). Results Hierarchical cluster analysis (HCA) and principal component analysis (PCA) were able to remarkably distinguish walnut oil produced by different roasting processes. In addition, correlation analysis showed that there was a significant impact among indicators. There were 73 VOCs were identified in the optimum roasted treated walnut oil, consisting of 30 aldehydes, 13 alcohols, 11 ketones, 10 esters, 5 acids, 2 oxygen-containing heterocycles, 1 nitrogen-containing heterocycle and 1 other compound. GC-IMS results showed that aldehydes contributed significantly to the volatile flavor profile of walnut oil, especially (E)-2-heptenal, (E)-2-pentenal and hexenal. Discussion The properties of walnut oil based on varying roasting pretreatment of walnut kernels were significantly differentiated. Roasting at 120°C for 20 min is a suitable pretreatment roasting condition for pressing walnut oil. Roasting at 120°C for 20 min is a suitable pretreatment roasting condition for pressing walnut oil.